A protein fragment of Rv3194c located on mycobacterial cell surface efficiently prevents adhesion of recombinant Mycobacterium smegmatis, and promises a new anti-adhesive drug. (December 2020) - Zhao, Dongyue; Lin, Danfeng; Xu, Chen
Abstract: Adhesins are virulence factors expressed on the surfaces of pathogenic bacteria that mediate pathogen-host interactions, a critical step in the infection process. Here, we show that the Mycobacterium tuberculosis protease Rv3194c functions not only as an enzyme but as an adhesin. The heterologous Rv3194c protein was purified from Escherichia coli and was shown to bind to hyaluronic acid (HA). The HA-binding site was identified as a 20 amino acid peptide between residues 91 and 110 (P91-110). Rv3194c bound to A549 alveolar basal epithelial cells and the interaction was abolished by the addition of hyaluronidase or P91-110. Experimental infection in vitro revealed that Rv3194c participates in the attachment of recombinant Mycobacterium smegmatis (Rv3194c/MS) to A549 cells, and P91-110 treatment of A549 cells largely inhibited the Rv3194c/MS-A549 cell interaction. To provide in vivo evidence, we constructed a reporter strain of M. smegmatis that expressed a derivative of the firefly luciferase that is shifted to red (FFlucRT) in combination with Rv3194c (Rv3194c + FFlucRT/MS) to infect mice and monitor the progression of the disease. In mice, Rv3194c dramatically enhanced M. smegmatis persistence and induced lesions in the lungs. In addition, treatment of intratracheal Rv3194c + FFlucRT/MS- infected mice with P91-110 significantly suppressed the growth of Rv3194c + FFlucRT/MS in vivo and reduced pathological injury caused by infection of the lung with Rv3194c + FFlucRT/MS. Taken together, these results demonstrate that Rv3194c functions as an HA-binding adhesin and that P91–110 may have the potential for treating and preventing mycobacterial infection. Highlights: Rv3194c is a hyaluronic acid (HA)-binding adhesin. 20 amino acids from 91 to 110 of Rv3194c (P91-110) is responsible for the specific HA-binding site of Rv3194c. Rv3194c efficiently facilitates mycobacterial-lung epithelial interaction through its HA-binding site. Peptide (P91-110), promising anti-adhesive drug, efficiently prevents adhesion of recombinant  Mycobacterium smegmatis.